2021
DOI: 10.3390/cancers13143400
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Immunotherapy for Adult Glioblastoma

Abstract: Despite aggressive multimodal therapy, glioblastoma (GBM) remains the most common malignant primary brain tumor in adults. With the advent of therapies that revitalize the anti-tumor immune response, several immunotherapeutic modalities have been developed for treatment of GBM. In this review, we summarize recent clinical and preclinical efforts to evaluate vaccination strategies, immune checkpoint inhibitors (ICIs) and chimeric antigen receptor (CAR) T cells. Although these modalities have shown long-term tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 141 publications
2
7
0
Order By: Relevance
“…The first published report of the CheckMate 498 trial (n=560) showed no difference in patient survival after treatment with nivolumab combined with RT compared with TMZ plus RT, where the mOS for both combinations was approximately 14 months. 63 , 64 Similar preliminary results were obtained for the CheckMate 548 trial (n=693), which showed no significant statistical improvement in OS or PFS after combination treatment with nivolumab and TMZ plus RT. 63 , 65 Furthermore, ongoing phase II study (NUTMEG) evaluates whether nivolumab combined with TMZ improves OS in newly diagnosed GBM in elderly patients (65 years of age and/or older) (NCT04195139).…”
Section: Immune Checkpoint Inhibitors and Potential New Checkpoint Bl...supporting
confidence: 62%
See 1 more Smart Citation
“…The first published report of the CheckMate 498 trial (n=560) showed no difference in patient survival after treatment with nivolumab combined with RT compared with TMZ plus RT, where the mOS for both combinations was approximately 14 months. 63 , 64 Similar preliminary results were obtained for the CheckMate 548 trial (n=693), which showed no significant statistical improvement in OS or PFS after combination treatment with nivolumab and TMZ plus RT. 63 , 65 Furthermore, ongoing phase II study (NUTMEG) evaluates whether nivolumab combined with TMZ improves OS in newly diagnosed GBM in elderly patients (65 years of age and/or older) (NCT04195139).…”
Section: Immune Checkpoint Inhibitors and Potential New Checkpoint Bl...supporting
confidence: 62%
“… 63 , 64 Similar preliminary results were obtained for the CheckMate 548 trial (n=693), which showed no significant statistical improvement in OS or PFS after combination treatment with nivolumab and TMZ plus RT. 63 , 65 Furthermore, ongoing phase II study (NUTMEG) evaluates whether nivolumab combined with TMZ improves OS in newly diagnosed GBM in elderly patients (65 years of age and/or older) (NCT04195139). Currently, there is recruitment of patients for a phase II study designed to determine the potential of increased therapeutic effect of nivolumab combined with RT and bevacizumab in recurrent MGMT-methylated GBM (NCT03743662).…”
Section: Immune Checkpoint Inhibitors and Potential New Checkpoint Bl...supporting
confidence: 62%
“…The development of novel immunotherapeutic strategies to engage the immune system to treat GBMs have provided renewed hope for improving patient outcomes ( 67 , 68 ). GBMs are typically classified as an immunologically cold tumor ( 69 ) and contain T cells at low abundance ( 70 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though there have been limited advances in the progression of GBM therapeutics to significantly increase patient survival compared to other cancers, this has not dampened the motivation of researchers and clinicians to investigate novel treatment strategies for combating this disease. The Special Issue, ‘Novel Treatment Strategies for Glioblastoma’ [ 3 ], contains twelve articles (five original research articles and seven reviews) that explore a range of novel and strategic approaches for improving the treatment of GBM [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. This editorial aims to briefly summarize the content of these articles.…”
mentioning
confidence: 99%
“…As current treatment strategies have not delivered significant improvements in GBM patient survival, some emerging therapeutics have redirected their efforts towards reprogramming the patient’s immune system to generate an anti-tumor response. The review by Chokshi et al [ 11 ] focuses on evaluating several immunotherapeutic approaches that have been trialed for the treatment of GBM, including various vaccination strategies, immune checkpoint inhibitors (ICIs) and chimeric antigen receptor (CAR) T cells. The exposure of tumor-associated antigens to antigen-presenting cells, which activate immune effector cells to achieve an anti-cancer immune response, form the framework of cancer vaccine functionality.…”
mentioning
confidence: 99%